Doubts on Kissinger´s method of kinetic evaluation based on several conceptual models showing the difference between the maximum of reaction rate and the extreme of a DTA peak - Šestak, Jaraslav; Holba, Pavel; Živkovič, Živan (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
The famous Kissinger´s kinetic evaluation method (Anal. Chem. 1957) is examined with respect to the feasible impact of the individual quantities and assumptions involved, namely the model of reaction mechanism, f(a) (with the iso- and noniso-thermal degrees of conversion, a and l) the rate constant, k(T) (and associated activation energy, E), heating/cooling rate, b (supplementing additional thermodynamic term for the melt undercooling, DT) and above all, the association of the characteristic temperature, Tm , with the DTA peak apex. It is shown that the Kissinger´s equation, in contrary to the results of Vold (Anal. Chem. 1949), is omitting the term of heat inertia arising from the true balance of heat fluxes. The absence of this term skews the evaluated values of activation energies.